SINTESIS ADSORBEN ZEOLIT@AuNPs@MET MENGGUNAKAN EKSTRAK DAUN BINAHONG (Anredera cordifolia) SEBAGAI BIOREDUKTOR PREKURSOR Au DAN KARAKTERISASINYA (Synthesis Zeolite@AuNPs@MET Adsorbent by Binahong (Anredera cordifolia) Leaf Extract as Au Precursor Bioreduc - Nurdiani, Nurdiani; Darusman, Latifah K.; Rohaeti, Eti (Baristand Industri Banda Aceh, 2015)
Modifying zeolite with Au nanoparticles and mercaptoethanol ligand(zeolite@AuNPs@MET) has been developed as an adsorbent of heavy metal ions. The preparation ofzeolite@AuNPs@MET composite material was done in three steps. Firstly, incorporating gold precursorin to zeolite cavity. Secondly, reduction of gold nanoparticles by binahong leaf extract. Thirdly, modifyingzeolite@AuNPs with mercaptoethanol ligand. Binahong was used as bioreductor agent in the synthesis ofAu nanoparticles since it has large contents of flavonoids, saponins, tannins, and steroids which containreducing functional group. The zeolite@AuNPs@MET composite material was characterized by XRD,EDX, PSA, TEM, FTIR and UV Visible Spectrophotometer. EDX measurements showed Au content of0.88%, TEM and PSA measurement showed Au nanoparticle size in the range of 7.12 nm to 14.45 nmwith an average size distribution of 110.6 nm while gold nanoparticles immobilized in the pores ofzeolites have sizes ranging from 4.98 nm to 9.50 nm with an average size distribution of 279 nm. UVVisible absorption spectrum revealed a new formed peak at 537 nm, indicating formation of AuNPs. The characteristic peaks (at 526 nm and 532 nm) were also found in the UV-Vis absorption spectrum ofAuNPs immobilized in the zeolite pores and AuNPs in the zeolite@AuNPs@MET composite, respectively.FTIR measurements of mercaptoethanol ligand showed the presence of a peak at 2550 cm-1 regionindicating SH functional groups, which disappeared after modification of zeolite@Au with MET ligand,indicated the âSH bond was broken and the remained âS was attached to AuNPs. All of thecharacterization revealed the success of the composite material preparation, which is an interestingmaterial expected to have highly potential as a heavy metal ion adsorbent.